(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Shakespeare’s playshave been universally praised for centuries. However, Titus Andronicus was notincluded in this positive evaluation until the second half of the 20th century,when mainly feminist criticism contributed to an academically kinderre-assessment of this generally gory play. This paper, focusing on the issuesof aesthetic value and the deletion of empathy, proposes a defamiliarized, adifferent reading of this Shakespearean play, from the perspective of theJapanese people, ‘famous’ for aesthetically enjoying the cathartic showing ofgratuitous violence.